2014
DOI: 10.1186/2051-1426-2-s3-p210
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anti-tumor effects of the PD-1/PD-L1 blockade by combining a highly absorptive form of NF-kB/STAT3 inhibitor curcumin

Abstract: The PD-1/PD-L1 blockade is now recognized as one of the basic immune interventions for development of combination cancer immunotherapy. We have been screening chemical libraries to obtain compounds which have an activity to augment anti-tumor activity of the PD-1/PD-L1 blockade. We have previously shown that activation of NF-kB and STAT3 signals in both cancer cells and immune cells plays important roles in cancer cell-induced immunosuppression, and their inhibition may augment anti-tumor CTL. Curcumin, a majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…To remodel the microenvironment, it is also necessary to get help from a drug that could play pivotal roles not only in killing tumor cells but also in dealing with the immune environment such as reducing MDSCs 13 or downregulation of STAT3. 14,15 Curcumin (CUR), a component of turmeric and one of the oldest natural polyphenols in traditional Asian medicine, is such a chemodrug. 16,17 As a well-known JAK-STAT3 pathway inhibitor, 14,15,18 CUR inhibits MDSCs in the spleen and tumor tissue in breast cancer models 19 and 3LL Lewis lung cancer models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To remodel the microenvironment, it is also necessary to get help from a drug that could play pivotal roles not only in killing tumor cells but also in dealing with the immune environment such as reducing MDSCs 13 or downregulation of STAT3. 14,15 Curcumin (CUR), a component of turmeric and one of the oldest natural polyphenols in traditional Asian medicine, is such a chemodrug. 16,17 As a well-known JAK-STAT3 pathway inhibitor, 14,15,18 CUR inhibits MDSCs in the spleen and tumor tissue in breast cancer models 19 and 3LL Lewis lung cancer models.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Curcumin (CUR), a component of turmeric and one of the oldest natural polyphenols in traditional Asian medicine, is such a chemodrug. 16,17 As a well-known JAK-STAT3 pathway inhibitor, 14,15,18 CUR inhibits MDSCs in the spleen and tumor tissue in breast cancer models 19 and 3LL Lewis lung cancer models. 20 However, its lipophilic nature and relatively low solubility in aqueous solutions create a major challenge in clinical applications as a potent anticancer agent.…”
Section: Introductionmentioning
confidence: 99%
“…The strategy potently improved the cellular uptake and cytotoxicity of curcumin [76]. The combination of curcumin and an anti-PDL1 antibody was found to exert synergistic anti-tumor activity in an ovarian cancer mouse model, indicating that curcumin may indeed serve as an integrative component of current immunotherapy [77]. Meanwhile, a multi-center, open-label, non-randomized, 3-cohort phase 2 study has enrolled patients with recurrent/refractory cervical carcinoma, endometrial carcinoma, or uterine sarcoma.…”
Section: Curcumin-triggered Immune Responsementioning
confidence: 98%
“…Moreover, Hayakawa et al found that curcumin administration in the colon cancer mouse model significantly increased the tumor antigen-specific CD8 + T cell induction as well as enhanced the T cell stimulatory activity of dendritic cells (DCs) by downregulating NF-κB and STAT3 signaling pathways. They also revealed that combining curcumin with an anti-PD-L1 antibody had a synergistic tumor-suppressive effect [110]. Shao et al established mouse models bearing subcutaneous or metastatic bladder cancer and found that bisdemethoxycurcumin, an analog of curcumin, in combination treatment with an anti-PD-L1 antibody could significantly upregulate the secretion of IFN-γ and granzyme B and decrease the number of MDSCs, which successfully boosted immune response and prolonged mouse survival [113].…”
Section: Non-flavonoids Curcuminmentioning
confidence: 99%